2017
DOI: 10.1016/j.molbiopara.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A DiCre recombinase-based system for inducible expression in Leishmania major

Abstract: Here we present the establishment of an inducible system based on the dimerizable Cre recombinase (DiCre) for controlled gene expression in the protozoan parasite Leishmania. Rapamycin-induced DiCre activation promoted efficient flipping and expression of gene products in a time and dose-dependent manner. The DiCre flipping activity induced the expression of target genes from both integrated and episomal contexts broadening the applicability of the system. We validated the system by inducing the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A background cell line was established in which DiCre is expressed from the ribosomal locus, while both Cas9 and T7 polymerase are expressed from the tubulin array. For this, WT cells were transfected with plasmid pGL2339 [ 80 ], previously digested with Pac I and Pme I, to generate DiCre-expressing cells. Correct integration into the ribosomal locus was confirmed by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…A background cell line was established in which DiCre is expressed from the ribosomal locus, while both Cas9 and T7 polymerase are expressed from the tubulin array. For this, WT cells were transfected with plasmid pGL2339 [ 80 ], previously digested with Pac I and Pme I, to generate DiCre-expressing cells. Correct integration into the ribosomal locus was confirmed by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The DiCre (pGL2339 (20)) and HUS1 Flox -expressing constructs were generated by gateway recombination reactions. For the DiCre construct, a BP reaction was performed to introduce the 5′SSU (253 bp) and 3′SSU (955 bp) homology sequences into pDONR P41-Pr and pDONR P2rP3 vectors, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that HUS1 is involved in the Leishmania major response to genotoxic stress (17,18), but the roles that are critical for the parasite’s survival have not been determined. In this study, we have adapted the DiCre-mediated gene deletion system (19,20) to be used in L. major and reveal the essentiality of HUS1. We have advanced our understanding of HUS1 function at the G2/M checkpoint by demonstrating that its absence leads to aberrant mitosis onset in the presence of DNA damage in both unperturbed and replication-stressed cells.…”
Section: Introductionmentioning
confidence: 99%
“…The repair of the double strand breaks (DSB) at the 5′ and 3′ ends of the GOI allows the integration of the LoxP sequences and resistance cassettes to generate a Floxed targeted gene cell line (Figure 1c). These edited parasites are obtained after a single round of transfection, which generally takes 8–10 days, making this method highly efficient and time‐saving compared with the previously published conditional KO method (Santos et al, ). In some cases, most probably because certain genes cannot tolerate untranscribed region (UTR) modifications, the strategy in which the GOI is directly flanked by LoxP sequences showed limited efficiency; and edited parasites with modified UTRs did not recover after transfection or exhibited growth defects and/or phenotype changes before induction.…”
Section: Resultsmentioning
confidence: 99%